Description of two new species of Dysidea (Porifera, Demospongiae, Dictyoceratida, Dysideidae) from Tauranga Harbour, Bay of Plenty, New Zealand - Cormack, Samuel P. Mc; Kelly, Michelle; Battershill, Christopher N. (Zootaxa, 2020)
Differentiation of species within the genus Dysidea Johnston, 1842 (Order Dictyoceratida Minchin, 1900, Family Dysideidae Gray, 1867) is extremely difficult as they lack spicules which are strongly diagnostic in other Demospongiae, and their primary and secondary fibres and the mesh that they form, may be irregular in shape and thickness, thus difficult to measure for comparisons. Here we review species of Dysidea known from the New Zealand Exclusive Economic Zone (EEZ), validating five species: Dysidea cristagalli Bergquist, 1961a, from the Hauraki Gulf; D. hirciniformis (Carter, 1885a) sensu Dendy (1924), from North Cape; D. navicularis Lendenfeld, 1888, from Port Lyttleton on the east coast of the South Island; D. ramsayi (Lendenfeld, 1888) from the Chatham Islands; D. spiculivora Dendy, 1924, from Cape Maria Van Diemen and the Three Kings Islands to the north of New Zealand. Dysidea fragilis (Montagu, 1818) sensu Bergquist (1961b), from Mernoo Bank on Chatham Rise, is now considered to be invalid, and D. elegans (Nardo, 1847) sensu Brøndsted (1927), from the Coromandel Peninsula, is considered unrecognisable. Several partially characterised species have also been cited in the literature. Two new species from Tauranga Harbour, on the northeast coast of the North Island, Dysidea tuapokere sp. nov. and D. teawanui sp. nov., are described. These descriptions are based on fresh material and in situ photography, facilitating clear, informative descriptions, that will enable ease of identification of these species in the future.